Use of potentially dangerous drugs in an Intensive Care Unit (Research, Society and Development, 2020)
Objectives: To analyze the use of potentially dangerous drugs in an intensive care unit. Methods:  Cross-sectional study, observational, performed in an intensive care unit of a university hospital in Rio de Janeiro. Data were collected from March to June 2018.  The first stage corresponded to the evaluation of 523 drug prescriptions, through a checklist to identify the most frequent potentially dangerous drugs, based on the list of the Institute for Safe Practices in the Use of Medicines. In the second stage, 248 observations were made at the bedside, seeking to identify the best practices, recommended in the investigated unit, for drug safety. The variables were: identification with the name of the drug in the infusion pumps and equipment, in addition to the warning signal on the equipment, with colors recommended in the unit of the study for this purpose. The data were analyzed through simple descriptive statistics and by inference, performed through R, with a significance level of 5%. Results:  There were 6,286 drugs in the prescriptions. Of these, 1,397 (22%) were considered potentially dangerous, the most commonly used being enoxaparin (256 - 18.3%). The frequency of potentially dangerous drugs was between 0 and 8.69. As regards good practices for drug safety, verificor that amongthe 443 infusion pumps observed; the name of the medicinal product was present in 441 (99.6%) of these and in 429 (96.8%) equipos. Salert inhalers were identified in 392 (88.6%) equipment. Conclusion: The highest frequency occurred with enoxaparin and intravenous infusion of potentially dangerous drugs occurred satisfactorily.